Peningkatan Kompetensi Guru dalam Pemanfaatan Teknologi Digital untuk Pengelolaan Pembelajaran di Yayasan Pendidikan Cerdas Mandiri - Sunday Ade Sitorus; Tri Melda Mei Liana; Winda Ardiani (Jurnal Informasi Pengabdian Masyarakat, 2026)
Community service at Yayasan Pendidikan Cerdas Mandiri was designed to improve teachers’ competence in utilizing digital technology for learning management. Initial observation showed that teachers were familiar with basic digital devices, but the use of technology was still limited to communication and simple administration. The program was arranged through socialization, training, technology implementation, mentoring, evaluation, and sustainability planning. Activities focused on selecting appropriate learning media, using digital applications for material delivery and assessment, and preparing simple digital learning tools. The expected outcomes include improved teacher understanding of digital learning, better practical skills in using learning applications, and the availability of examples of digital teaching materials and assessment instruments. This article presents a systematic narrative of the in the format of a community service journal manuscript, emphasizing the link between partner problems, offered solutions, implementation methods, and expected social change in educational services.